2012
DOI: 10.4067/s0718-221x2012005000008
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of Moroccan olive stones by using it in particleboard panels

Abstract: ABSTRACTe main objective of this work was to nd new applications to valorize olive stones (endocarp and seed). In order to improve knowledge on olive stones, the phenolic compounds concentration of three varieties of Moroccan olive trees: Moroccan Picholine, Menara and Haouzian were studied. Olive stones of three varieties were characterized by Fourier Transform Mid Infrared Spectroscopy (FT-MIR). Total phenolic compounds are quanti ed a er solid-liquid extraction by an assay of Folin-Ciocalteu. Moroccan Picho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…To enhance the quality of used cooking oils, oils should be remediated using various remediating materials such as carbonaceous and inorganic adsorbents [7,10]. Among the variety of different adsorbents is activated carbon, which takes a leading position as an adsorbent for the removal of various toxic pollutants due to its excellent adsorption ability [15][16][17][18][19][20][21][22][23][24][25][26][27]. Activated carbons are known to have a large surface area, polar functional groups, and microporous structure, hence, it is not effective in removing polar substances from used frying oil and does not allow efficient purification.…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the quality of used cooking oils, oils should be remediated using various remediating materials such as carbonaceous and inorganic adsorbents [7,10]. Among the variety of different adsorbents is activated carbon, which takes a leading position as an adsorbent for the removal of various toxic pollutants due to its excellent adsorption ability [15][16][17][18][19][20][21][22][23][24][25][26][27]. Activated carbons are known to have a large surface area, polar functional groups, and microporous structure, hence, it is not effective in removing polar substances from used frying oil and does not allow efficient purification.…”
Section: Introductionmentioning
confidence: 99%
“…So far, its main route of valorization is its use as biofuel, due to its high energy content, generating ashes after combustion as a waste [ 17 , 18 ]. Research is currently being carried out on other ways of valorization: (a) in biorefinery, due to its high carbohydrate content [ 19 ], and (b) its incorporation as part of composite materials, such as the materials with which chipboard panels are manufactured [ 20 ]. Figure 1 shows a general overview of those processes involved in obtaining OP, as well as some of the feasible ways to valorize them.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the phenolic composition, Fernández-Bolaños et al (1998) identified for the first time tyrosol and hydroxytyrosol as the main phenolic compounds found in the fraction of steamexploded olive stones. Hydroxytyrosol, the most powerful antioxidant in olive fruit, is able to inhibit or delay the rate of growth of a wide range bacteria and microfungi (Elbir et al, 2012). As an interesting approach, partial removal of extractives such as phenolic compounds can offer the double benefit of recovering bioactive products with antioxidant capacity and to reduce the toxicity of the prehydrolyzates, increasing the performance of further bioprocess steps.…”
Section: Introductionmentioning
confidence: 99%